Conceptual implementation of a data logger with a graphical user interface data extraction program - Ahmad Shukri Fazil Rahman Fazil Rahman; Samila Mat Zali; Shamshul Bahar Yaakob; Abdul Rahim Abdul Razak; Mohd Zamri Hasan; Siti Hajar Mohd Tahar (Institute of Advanced Engineering and Science, 2019)
A Graphical User Interface (GUI) design was developed to extract data from a data logger. The low-cost data logger was developed using a common pic18f4550 microcontroller. Simple data recording feature is implemented by using the Electrically Erasable Programmable Read-Only Memory (EEPROM) module from the microcontroller unit. The GUI software employed VB.net 2013 and has been tested to work in window 10 environment. Simulation work was performed with temperature and humidity sensors using Proteus VSM software. Upon simulation, the GUI shows its capability of extracting measured data from the data logger and converting the data to a Comma-Separated Values, (CSV) format for further analysis.